The Boundary Conditions of High-Performance Work Systems–Organizational Citizenship Behavior Relationship: A Multiple-Perspective Exploration in the Chinese Context - Zhang, Bo; Liu, Lihua; Cooke, Fang Lee; Zhou, Peng; Sun, Xiangdong; Zhang, Songbo; Sun, Bo; Bai, Yang (Frontiers in Psychology, 2022)
This research synthesizes social exchange, organizational culture, and social identity theories to explore the boundary conditions of the relationship between high-performance work systems and employee organizational citizenship behavior. In particular, it draws on the China-specific management context. In this country, in spite of the wide use of a long-term-oriented and loose-control-focused Western-styled strategic human resource management (HRM) model, a short-term-focused and tight-control-oriented error aversion culture is still popular. The study uses multi-source individual-level survey data in a large state-owned enterprise to test the hypotheses. It is found that employee-experienced, Western-styled high-performance work systems positively impact a China-specific employee’s organizational citizenship behavior (OCB), and the—joint—moderation effects of employee-perceived error aversion culture and organizational identification are significant. The research findings deepen the understanding of the HRM-OCB relationship by demonstrating that culture and identity can jointly adjust the effects of HRM on OCB. The findings also challenge an established argument in the HRM-OCB literature that compatibility between employees’ personalities and organizational values – organizational identification – can enhance OCB.